Rubber Crumb Infill in Synthetic Turf and Health Outcomes: A Review of the Literature on Polycyclic Aromatic Hydrocarbons and Metalloids - Shamshad Karatela; Igor Popovic; Zahra Sobhani; Shiv Basant Kumar; Thava Palanisami; Li-Zi Lin; Gunther Paul (Epidemiologia)
Synthetic turf has become a popular alternative to natural grass due to low upkeep costs; however, its health impacts have not been clearly elucidated. This review examines and consolidates the existing literature on rubber crumb in infill in synthetic turf and its associated adverse health outcomes, along with recommendations for future research. A database search was conducted in PubMed, Web of Science, Scopus, Embase, and Google Scholar of studies on exposures to rubber crumb in infills in synthetic turf. The search focused on epidemiological and toxicological laboratory studies (including exposure simulation and animal studies), as well as government reports. Non-English studies and those addressing injuries (musculoskeletal and burn injuries) were not considered. Eighteen laboratory studies examined concentrations of PAHs found in synthetic turf rubber infill. The total level of PAHs detected in samples varied between 0.4 mg/kg and 3196 mg/kg. The PAH levels were influenced by the age of the synthetic turf, with the older synthetic surface fields containing lower concentrations (compared to newly laid turfs). Synthetic turfs composed of industrial rubber crumb infill also had a lower PAH composition relative to end-of-life tyre-derived infill. In the six studies that investigated the metal content and composition of rubber crumb infill, Aluminium (5382 mg/kg), Zinc (5165 mg/kg), and Iron (489.6 mg/kg) had the highest median concentrations. There were minor differences in heavy metal concentrations found in newly installed synthetic turf compared to older turfs and synthetic sporting fields exposed to direct sunlight (versus indoor fields). There were two epidemiological studies on synthetic turf rubber crumb infill (one ecological and one cross-sectional study), which found no significant associations between synthetic turf exposure and the incidence of leukemia, non-Hodgkin lymphoma, and Hodgkin lymphoma. Similarly, one metabolomic study of urine samples from athletes taken pre- and post-match on synthetic turf, and two studies simulating dermal, ingestion, and inhalation exposure concluded that there was no elevated health risk associated with playing on synthetic turf pitches. Currently, there is very limited evidence of an association between synthetic turf use and adverse health outcomes. Considering the ubiquitous use of synthetic grass globally and the scarcity of epidemiological studies, there is a vital need for further research based on longitudinal study designs and more robust exposure assessments, to help improve our understanding of any potential health risks associated with synthetic turf infill exposures.